Dispatch Reliability in Commercial Aviation Maintenance Operations: Quantifying Delay Risk under Fault Uncertainty, MEL Governance, and Spare-Part Constraints - Lim Wei Jun Lim Wei Jun; Tran Minh Khoa Tran Minh Khoa; Ploy S. Rattanakul Ploy S. Rattanakul (Kalam Practica Media, 2025)
This article presents a reliability-centered engineering framework that treats maintenance dispatch as an end-to-end decision pipeline, explicitly modeling uncertainty propagation from fault detection and diagnostic confidence through MEL deferral decisions, spares availability, maintenance task duration variability, and crew scheduling constraints into distributional outcomes that operations manage, including probability of delay exceeding defined thresholds, expected delay minutes per departure, probability of cancellation, time-to-release distributions, and nuisance troubleshooting burden. A scenario-based quantitative study is developed for a representative narrow-body fleet operating a hub-and-spoke schedule, comparing four dispatch decision architectures: baseline reactive troubleshooting, enhanced diagnostics without governance, risk-based dispatch supported by confidence scoring, and a governance-optimized two-tier approach that constrains nuisance maintenance actions while preserving safety and compliance through standardized MEL decision rules, verification triggers, and spare-part risk pooling. Results show that (i) tail delay outcomes are dominated by diagnosis and spares-induced recovery latency rather than by mean task time, (ii) increased diagnostic messages without governance can increase nuisance actions and worsen punctuality, and (iii) the strongest reliability gains come from standardizing decision governance and aligning escalation with evidence confidence rather than from analytics alone. The paper provides up to three copy-ready tables and full prompts for data-driven figures suitable for Techne submission.